The Status of Neigbhourliness in the Quran and Sunnah - Klaina, Mekki (International Journal of Education, Culture, and Society, 2025)
This study addresses the human dimension in Islam, which seeks to promote harmony and cooperation among people by encouraging mutual respect and working together for the common good. The significance of this topic lies in Islam’s emphasis on fostering good conduct, preserving the rights of neighbours, and promoting social solidarity, recognising that the concept of neighbourhood extends beyond simple proximity. The study highlights the importance of neighbourly rights as outlined in the Qur'an and Sunnah, illustrating how respecting these rights contributes to achieving social peace. It also discusses the consequences of neglecting these rights, including social fragmentation, weakened faith, and social unrest. The study employs an analytical approach to understand the texts and their implications, focusing on Quranic verses, Prophetic traditions, and relevant Islamic sources concerning neighbourly rights. It also draws on the methodology of Hadith scholars to assess the authenticity of the narrations when necessary, acknowledging that some narrations may be weak but do not reach the level of fabricated Hadiths, as the study focuses on values rather than legal rulings. The study concludes that safeguarding neighbourly rights, as stipulated in the Qur'an and Sunnah, is an essential part of Islamic ethics, whether for Muslims or non-Muslims. It stresses that neglecting these rights leads to social discord and weakens community ties. The study also highlights Islam's vital role in encouraging ethical behaviour, cooperation, and coexistence among individuals and nations. The conclusion reiterates that reform must begin with self-improvement, followed by family, and then extend to the broader community—an individual who is both good and reformative is better than one who is simply good.